Dynamics of Organic Open Space : Transformation Functions and Activities on the Nunbaun Sabu Coast , Kupang City - Jeni Messakh; Yohanes A. Luwu (Asosiasi Dosen Muda Indonesia, 2025)
Public open spaces (POS) in coastal areas often develop organically without formal planning, yet play a critical role in the social life of urban communities. This study examines the transformation of the organic public open space at Nunbaun Sabu Beach, Kupang City, Indonesia. The aim of this research is to identify the factors driving the functional transformation of this coastal space and the patterns of social activities occurring within it. A qualitative approach was adopted, using case study methodology, including field observations and in-depth interviews. The findings indicate that the space has shifted from parking lot for churchgoers to a public social space for recreation and social interactions. The transformation is largely driven by the construction of a coastal defense wall (500 meters long), which provided a sense of safety and enhanced the area’s attractiveness for social activities. The beautiful sunset view further entices visitors to engage in activities such as resting, gathering, and enjoying the natural scenery. This study also emphasizes how physical infrastructure, such as the coastal defense wall and the sunset view, plays a critical role in the transformation of this organic public open space, as framed by Michel de Certeau’s theory of space manipulation and Lefebvre’s theory of the production of space. The findings offer valuable insights for urban planning that is more responsive to organically developed public spaces.